Hubungan Dukungan Sosial dengan Kecemasan dan Depresi pada Pasien Kanker Payudara di RSU Raden Mattaher Jambi - Yuliana Yuliana; Mustikasari Mustikasari; Feri Fernandes (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Breast cancer is the most common cancer in woman. In Europen there are approximately 175,000 cases found regarding breast cancer and more than 165,000 patients died if the cancer is not controlled, whereas in the United States 44,000 patients died of breast cancer. According to the Hospital Statistics in the Breast Cancer Hospital Information System, Indonesia is the first rank of the most breast cancer patients which can be found in almost every hospital in Indonesia. The impact of breast cancer on the aspects of bio- psycho- social- spritual in breast cancer patients include anxiety and depression.Unfortunately this study is not commonly carried aut by researchers. One effort to reduce anxiety and depression in breast cancer patients is to provide social support. This study aims to determine the relationship of social support with anxiety and depression in breast cancer patients. The method used is analytic cross- sectional study.Also this study is conducted at Raden Mattaher Hospital in Jambi, with 97 breast cancer patients were picked as participants. Data sampling that is utilised in this study was incidental sampling.The data were colleted by using several methods, such as the Multidemensional Scale of Perceived of Social Support (MSPSS) instrument, and the Hospital Anxiety and depression Scale (HADS), and later those data were analysed with Bivariate Analysis using the Chi Square test. The results showed that the average age of breast cancer patient is 46,57, length of diagnosis is 28,59 months, low education level patient is 68,0%, patient who has merried is 91,8%, unemployed patient is 78,4%, patient who reseived good social support is 54,6%, patient with anxiety is 49,5%, and patient with depression is 50,5%. There is relationship between social support and anxiety in breast cancer patients, with (p:0,000).